2015
DOI: 10.1002/ajmg.a.37273
|View full text |Cite
|
Sign up to set email alerts
|

Myhre syndrome: Clinical features and restrictive cardiopulmonary complications

Abstract: Myhre syndrome, a connective tissue disorder characterized by deafness, restricted joint movement, compact body habitus, and distinctive craniofacial and skeletal features, is caused by heterozygous mutations in SMAD4. Cardiac manifestations reported to date have included patent ductus arteriosus, septal defects, aortic coarctation and pericarditis. We present five previously unreported patients with Myhre syndrome. Despite varied clinical phenotypes all had significant cardiac and/or pulmonary pathology and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…Pericardial disease (9, 17%) was usually a recurrent, chronic and occasionally lethal disease, with only one patient [Michot et al, ] reported as an “isolated episode.” Five (56%) of those with pericardial disease could be viewed as having LAPS. We classified the remaining nine patients as either as constrictive (4, 7%) or having chronic effusions (4, 7%), and for the sake of this discussion, include in this discussion the patient with epicarditis reported by Starr et al []. Seven (78%) of those affected were 18 years and younger.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pericardial disease (9, 17%) was usually a recurrent, chronic and occasionally lethal disease, with only one patient [Michot et al, ] reported as an “isolated episode.” Five (56%) of those with pericardial disease could be viewed as having LAPS. We classified the remaining nine patients as either as constrictive (4, 7%) or having chronic effusions (4, 7%), and for the sake of this discussion, include in this discussion the patient with epicarditis reported by Starr et al []. Seven (78%) of those affected were 18 years and younger.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of cardiovascular abnormalities were noted in 54% of the patients in the largest series of 32 patients [Michot et al, ], which was followed by detailed reporting of pericardial disease [Picco et al, ], and possible treatment with losartan [Piccolo et al, ]. Recently, abnormal wound healing with an exuberant fibroproliferative response during operative procedures, including orthotopic heart transplantation for restrictive cardiomyopathy (RCM) [Starr et al, ], has been highlighted as an important management issue.…”
Section: Introductionmentioning
confidence: 99%
“…Restricted joint mobility and scarring abnormalities are striking features of the disorders (Caputo et al, ; Le Goff et al, ; Lin et al, ). Cardiovascular abnormalities include restrictive cardiomyopathy and pericardial disease although congenital heart defects have also been reported (Lin et al, ; Starr et al, ). Patients with Myhre syndrome might develop various long‐term and life‐threatening complications including systemic hypertension, cardiomyopathy, pericarditis, laryngo‐tracheal stenosis, and pulmonary insufficiency (Garavelli et al, ; Lin et al, ; Starr et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…[12] Myhre syndrome, a connective tissue disorder characterized by deafness, restricted joint movement, compact body habitus, and distinctive craniofacial and skeletal features, is caused by heterozygous mutations in SMAD4. [13] Cardiac manifestations in Myhre syndrome included PDA, septal defects, aortic coarctation, and pericarditis. [13] As both siblings in this report grew up normally (i.e., without mental, skeletal, or facial abnormalities), involvement of the aforementioned genetic syndromes is unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Cardiac manifestations in Myhre syndrome included PDA, septal defects, aortic coarctation, and pericarditis. [13] As both siblings in this report grew up normally (i.e., without mental, skeletal, or facial abnormalities), involvement of the aforementioned genetic syndromes is unlikely.…”
Section: Discussionmentioning
confidence: 99%